Measuring dementia knowledge in German: validation and comparison of the dementia knowledge assessment scale, the knowledge in dementia scale, and the dementia knowledge assessment tool 2 - Melchior, Florian; Teichmann, Birgit (Journal of Alzheimer's disease, 2023)
Background: Assessing dementia knowledge is critical for developing and improving effective interventions. There are many different tools to assess dementia knowledge, but only one has been validated in German so far. Objective: To validate two tools
Gesehen am 05.09.2023